2011
DOI: 10.1016/j.otsr.2011.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous management of thoracolumbar burst fractures: Evolution of techniques and strategy

Abstract: Level IV. Retrospective observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 17 publications
0
41
0
1
Order By: Relevance
“…Patient and occupational exposure to radiation remains an issue, requiring adequate surgeon education in order to minimise the need for fluoroscopy use [28]. Fusion with minimal posterior surgery is not possible, which necessitates late instrumentation removal [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Patient and occupational exposure to radiation remains an issue, requiring adequate surgeon education in order to minimise the need for fluoroscopy use [28]. Fusion with minimal posterior surgery is not possible, which necessitates late instrumentation removal [29]. …”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Blondel et al [9] presented in their retrospective observational study. The results of this study support the growing interest in minimally invasive techniques in management of spinal injuries without neurological deficit.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature prognostic factors described that may point to a failure of conservative treatment are not well [3-5, 7, 12]. Blondel et al [2] showed in the 2011, analyzing a cohort of 29 patients, that the surgical treatment with percutaneous kyphoplasty is a good option both in terms of symptoms and in term of correction of the kyphosis, in young and adult patients; From our point of view kyphoplasty is not the treatment of choice in recent fractures because the bone heals spontaneously when it is properly reduced, due to the physiological properties of elastic resistance of the trabecular bone of the vertebra, which the cement cannot mimic. Therefore, reserve this treatment for inveterate fractures.…”
Section: Discussionmentioning
confidence: 99%